Positive pole piece as well as preparation method and application thereof
By adding solid flame retardant and initiator to the positive electrode of the lithium-ion battery, the safety hazards of the battery at high temperatures are solved, and safety performance is improved and battery performance is maintained.
Patent Information
- Application Number
- CN202411933819.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
Smart Images

Figure BDA0005211350110000091 
Figure BDA0005211350110000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium-ion batteries and relates to a positive electrode sheet and a preparation method and application thereof. Background Art
[0002] At present, there are two solutions for the preparation of safe positive electrode sheets. The first mainstream preparation method is to add a certain amount of solid flame retardant to the positive electrode material, mix it with conductive agents and PVDF and other materials to prepare a slurry, and then coat and cold-press the positive electrode material to obtain a safe positive electrode sheet. The second method is to coat the positive electrode sheet with a solid flame retardant. The specific preparation method is to ultrasonically disperse the flame retardant after stirring, and then perform intermittent coating on the electrode coating machine, which can be evenly coated without spraying or dipping. Since this method has an inevitable disadvantage: increasing the impedance of the electrode, there is not much related research at present.
[0003] CN101252189A discloses a technology of doping ammonium polyphosphate into the active material of lithium-ion battery electrodes. This technology can form a complete, uniform and dense SEI film on the electrode during the cycle, thereby reducing the probability of SEI film decomposition and exothermic reaction at high temperature. However, once the SEI film is thermally decomposed, thermal runaway is inevitable. At the same time, ammonium polyphosphate is also a relatively expensive flame retardant additive.
[0004] CN103050706A proposes a maleimide additive for lithium batteries and a corresponding lithium battery positive electrode formula. The additive forms a protective film on the surface of the positive electrode active material, which can prevent the positive electrode active material from decomposing during an internal short circuit, making the battery safer. At the same time, due to the formation of a good safety protective film on the surface of the positive electrode active material, the service life of the lithium battery is improved, but the performance of the battery is significantly reduced.
[0005] CN107785578A proposes to use polymer-modified lithium carbonate to coat the positive electrode material, which can greatly improve the safety performance of lithium batteries. However, in the above patents, there is a contradiction between the amount of additives used and the safety performance. Excessive use will greatly reduce the energy density and seriously affect the cycle life, while a small amount will not achieve the desired effect.
[0006] Therefore, it is very necessary to develop a positive electrode sheet that does not affect battery performance and service life and has excellent safety performance. Summary of the invention
[0007] The object of the present invention is to provide a positive electrode plate and a preparation method and application thereof. The present invention adds a solid flame retardant and an initiator to the positive electrode plate, and greatly improves the safety performance of the positive electrode plate without affecting the performance of the positive electrode plate. The preparation cost of the positive electrode plate is low, the process route is simple, and the type of initiator can be selected as needed. The solid flame retardant and the initiator have good compatibility with the positive electrode active material.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a positive electrode plate, the positive electrode plate comprising a positive electrode current collector and a positive electrode active material layer disposed on the surface of the positive electrode current collector;
[0010] The positive electrode active material layer includes a positive electrode active material, a conductive agent, a binder, a solid flame retardant and an initiator.
[0011] The present invention adds a solid flame retardant and an initiator to the positive electrode plate. During the working process, the surface of the positive electrode plate will change in temperature. When the temperature reaches a certain temperature, the solid flame retardant can effectively play an insulating role at high temperature due to its own high boiling point, high flash point and non-flammable characteristics. At the same time, it decomposes at high temperature to produce free radical scavengers or halogen ions. The former can capture active substances required for combustion, remove free radicals and cut off the internal oxidation chain reaction of the battery. The latter reacts with polymer compounds to produce hydrogen halides, and hydrogen halides can react with active hydroxyl radicals (HO·) that proliferate in large quantities during the combustion of polymer compounds, so as to reduce their concentration and slow down the combustion speed until the flame is extinguished, thereby achieving a safe effect. At the same time, the initiator decomposes, and the decomposition product can accelerate the decomposition of the solid flame retardant to produce free radical scavengers or halogen ions to a certain extent, further improving the stability of the positive electrode plate. The initiator also has the characteristics of small dosage, significant effect and no by-products.
[0012] Preferably, the initiator comprises any one of an azo initiator, an organic peroxide initiator or a redox initiator, or a combination of at least two of them. Typical but non-limiting combinations include a combination of an organic peroxide initiator and a redox initiator, a combination of an azo initiator and a redox initiator, or a combination of an azo initiator and an organic peroxide initiator.
[0013] The decomposition temperature ranges of the azo initiator, organic peroxide initiator or redox initiator of the present invention are 50°C to 100°C, 50°C to 100°C, and 0°C to 50°C, respectively. These initiators can be selected in type and dosage according to different safety performance requirements of the battery. For example, if low-temperature safety requirements need to be met, redox pair initiators can be selected. If only high-temperature safety requirements are required, azo and organic peroxide initiators can be selected.
[0014] Preferably, the azo initiator includes any one of azobisisobutyronitrile, azobisisoheptanenitrile or dimethyl azobisisobutyrate, or a combination of at least two of them. Typical but non-limiting combinations include a combination of azobisisobutyronitrile and azobisisoheptanenitrile, a combination of azobisisoheptanenitrile and dimethyl azobisisobutyrate, or a combination of azobisisobutyronitrile and dimethyl azobisisobutyrate.
[0015] Preferably, the organic peroxide initiator comprises any one of benzoyl peroxide, t-butyl perbenzoate or cyclohexanone peroxide or a combination of at least two thereof, and typical but non-limiting combinations include a combination of benzoyl peroxide and cyclohexanone peroxide, a combination of t-butyl perbenzoate and cyclohexanone peroxide, or a combination of benzoyl peroxide and t-butyl perbenzoate, etc.
[0016] Preferably, the redox initiator comprises any one of potassium persulfate, thiol or sodium bisulfite or a combination of at least two thereof. Typical but non-limiting combinations include a combination of potassium persulfate and sodium bisulfite, a combination of thiol and sodium bisulfite, or a combination of potassium persulfate and thiol.
[0017] Preferably, the solid flame retardant includes a sulfur-based solid flame retardant and / or a halogen-based solid flame retardant, preferably a sulfur-based solid flame retardant and a halogen-based solid flame retardant.
[0018] Preferably, the median particle size D50 of the solid flame retardant is 10 nm to 100 nm, for example, 10 nm, 20 nm, 50 nm, 80 nm or 100 nm, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0019] Preferably, the mass ratio of the sulfur-based solid flame retardant to the halogen-based solid flame retardant is 1:(1-10), for example: 1:1, 1:2, 1:5, 1:8 or 1:10, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] Preferably, the sulfur-based solid flame retardant includes triphenyl thiophosphate.
[0021] Preferably, the halogen-based solid flame retardant includes brominated epoxy resin and / or brominated polystyrene.
[0022] Preferably, the positive electrode current collector comprises aluminum foil.
[0023] Preferably, the positive electrode active material includes any one of a ternary nickel-cobalt-manganese positive electrode material, a cobalt-free positive electrode material, a lithium cobalt oxide positive electrode material, a lithium iron phosphate positive electrode material or a lithium-rich manganese-based positive electrode material, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of a ternary nickel-cobalt-manganese positive electrode material and a cobalt-free positive electrode material, a combination of a ternary nickel-cobalt-manganese positive electrode material and a lithium-rich manganese-based positive electrode material, or a combination of a lithium iron phosphate positive electrode material and a ternary nickel-cobalt-manganese positive electrode material, etc.
[0024] Preferably, the conductive agent comprises conductive carbon black and / or carbon nanotubes.
[0025] Preferably, the binder comprises polyvinylidene fluoride.
[0026] Preferably, in the positive electrode active material layer, the mass ratio of the positive electrode active material, the conductive agent, the binder, the solid flame retardant and the initiator is (80-99):(0.1-10):(0.1-10):(0.1-10):(0.01-10), for example: 80:5:5:5:5, 90:4:4:1.5:0.5, 92:3:2:2:1, 96:0.5:0.5:2:1 or 99:0.1:0.1:0.7:0.1, etc., not limited to the listed values, other values not listed within the numerical range are also applicable.
[0027] Preferably, the mass ratio of the initiator to the solid flame retardant is 1:(1-10), for example: 1:1, 1:2, 1:5, 1:8 or 1:10, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] In a second aspect, the present invention provides a method for preparing the positive electrode sheet as described in the first aspect, the preparation method comprising the following steps:
[0029] (1) mixing a positive electrode active material, a conductive agent, a binder, a solid flame retardant, an initiator and a solvent, and dispersing them to obtain a positive electrode slurry;
[0030] (2) The positive electrode slurry is coated on the surface of the positive electrode current collector, and after post-treatment, the positive electrode sheet is obtained.
[0031] Preferably, the solvent in step (1) comprises N-methylpyrrolidone.
[0032] Preferably, the dispersing method in step (1) includes ball milling and / or ultrasonic dispersion.
[0033] Preferably, the post-processing in step (2) includes drying, cold pressing and slitting.
[0034] In a third aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet as described in the first aspect.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) The present invention adds a solid flame retardant and an initiator to the positive electrode plate, which greatly improves the safety performance of the positive electrode plate without affecting the performance of the positive electrode plate. The preparation cost of the positive electrode plate is low and the process route is simple. The type of initiator can be selected as needed. The solid flame retardant and the initiator have good compatibility with the positive electrode active material.
[0037] (2) The cycle expansion rate of the battery made of the positive electrode sheet of the present invention can be controlled within 8%, the retention rate can reach more than 86%, the discharge rate can reach more than 92%, the rate charging capacity retention rate can reach more than 94%, and it will not catch fire or explode in the needle puncture test. The battery surface temperature can reach below 38°C, and the hot box test can meet 130-140°C. The battery will not catch fire or explode within 30 minutes. The safe positive electrode sheet can meet the high temperature safety test. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0039] Example 1
[0040] This embodiment provides a positive electrode plate, which is prepared by the following method:
[0041] (1) NCM811 positive electrode active material, initiator, solid flame retardant, conductive agent, PVDF are mixed with N-methylpyrrolidone solvent in a mass ratio of 90:2:4:2:2, and a positive electrode slurry is obtained by ball milling. The initiator is benzoyl peroxide, the median particle size D50 of the solid flame retardant is 60 nm, the solid flame retardant includes triphenyl thiophosphate and brominated epoxy resin in a mass ratio of 1:5, and the conductive agent includes conductive carbon black and carbon nanotubes in a mass ratio of 1:1;
[0042] (2) The positive electrode slurry prepared in step (1) is coated on the surface of the aluminum foil, and the positive electrode sheet is obtained by drying, cold pressing and slitting.
[0043] Example 2
[0044] This embodiment provides a positive electrode plate, which is prepared by the following method:
[0045] (1) mixing a lithium cobalt oxide positive electrode active material, an initiator, a solid flame retardant, a conductive agent, and PVDF with an N-methylpyrrolidone solvent in a mass ratio of 92:2:3:2:1, and subjecting the mixture to ultrasonic dispersion treatment to obtain a positive electrode slurry, wherein the initiator is azobisisobutyronitrile, the solid flame retardant has a median particle size D50 of 30 nm, the solid flame retardant comprises triphenyl thiophosphate and brominated polystyrene in a mass ratio of 1:1, and the conductive agent comprises conductive carbon black and carbon nanotubes in a mass ratio of 1:1;
[0046] (2) The positive electrode slurry prepared in step (1) is coated on the surface of the aluminum foil, and the positive electrode sheet is obtained by drying, cold pressing and slitting.
[0047] Example 3
[0048] This embodiment provides a positive electrode plate, which is prepared by the following method:
[0049] (1) NCM811 positive electrode active material, initiator, solid flame retardant, conductive agent, PVDF are mixed with N-methylpyrrolidone solvent in a mass ratio of 92:2:4:1:1, and a positive electrode slurry is obtained by ball milling. The initiator is benzoyl peroxide, the median particle size D50 of the solid flame retardant is 20 nm, the solid flame retardant includes triphenyl thiophosphate and brominated epoxy resin in a mass ratio of 1:10, and the conductive agent includes conductive carbon black and carbon nanotubes in a mass ratio of 1:1;
[0050] (2) The positive electrode slurry prepared in step (1) is coated on the surface of the aluminum foil, and the positive electrode sheet is obtained by drying, cold pressing and slitting.
[0051] Example 4
[0052] The only difference between this embodiment and embodiment 1 is that the mass ratio of the initiator to the solid flame retardant is 1:0.5 (the total mass remains unchanged, that is, 4:2), and the other conditions and parameters are exactly the same as those in embodiment 1.
[0053] Example 5
[0054] The only difference between this embodiment and embodiment 1 is that the mass ratio of the initiator to the solid flame retardant is 1:15 (the total mass remains unchanged, that is, 0.375:5.625), and the other conditions and parameters are exactly the same as those in embodiment 1.
[0055] Example 6
[0056] The only difference between this embodiment and embodiment 1 is that the mass ratio of triphenyl thiophosphate to brominated epoxy resin is 1:0.5, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0057] Example 7
[0058] The only difference between this embodiment and embodiment 1 is that the mass ratio of triphenyl thiophosphate to brominated epoxy resin is 1:15, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0059] Example 8
[0060] The only difference between this embodiment and embodiment 1 is that no brominated epoxy resin is added, and other conditions and parameters are exactly the same as those in embodiment 1.
[0061] Example 9
[0062] The only difference between this embodiment and embodiment 1 is that triphenyl thiophosphate is not added, and other conditions and parameters are exactly the same as those in embodiment 1.
[0063] Comparative Example 1
[0064] The only difference between this comparative example and Example 1 is that no initiator is added, and the initiator is replaced by an equal amount of positive electrode active material. Other conditions and parameters are exactly the same as those in Example 1.
[0065] Comparative Example 2
[0066] The only difference between this comparative example and Example 1 is that no flame retardant is added, and the flame retardant is replaced by an equal amount of positive electrode active material. Other conditions and parameters are exactly the same as those in Example 1.
[0067] Comparative Example 3
[0068] The only difference between this comparative example and Example 2 is that no initiator is added, and the initiator is replaced by an equal amount of positive electrode active material. Other conditions and parameters are exactly the same as those in Example 2.
[0069] Comparative Example 4
[0070] The only difference between this comparative example and Example 2 is that no flame retardant is added, and the flame retardant is replaced by an equal amount of positive electrode active material. Other conditions and parameters are exactly the same as those in Example 2.
[0071] Performance Testing:
[0072] The safe positive electrode sheet and the negative electrode sheet made of carbon material that can be deintercalated with lithium are made into sheets, and then the core is obtained through the winding process. After packaging, the safe positive electrode sheet lithium-ion battery is obtained through the liquid injection, molding, formation and capacity division processes. We have conducted many electrical performance tests and safety performance tests on the battery to verify whether the safe positive electrode sheet improves safety performance without affecting other electrical performance. The specific test steps are as follows:
[0073] Rate charge and discharge test: leave the battery cell for 1 minute → discharge to 3.0V at 1.0C → leave for 10 minutes → charge to 4.5V at 1.0C, cut off at 0.02C → leave for 10 minutes → discharge to 3.0V using different currents (0.5C, 1C, 2C, 4C, 6C, 7C, 8C) → leave for 10 minutes, record the discharge capacity
[0074] Leave the battery cell for 1 minute → discharge at 1.0C to 3.0V → leave for 10 minutes → charge to 4.5V using different currents (0.5C, 1C, 2C, 4C, 6C, 7C, 8C), cut off at 0.02C → leave for 10 minutes → discharge at 1.0C to 3.0V → leave for 10 minutes, and record the discharge capacity;
[0075] Cycle test: First, pre-process the battery to test the thickness, voltage, internal resistance and other parameters before cycling, then set the charge limit voltage to 4.5V and the discharge minimum cut-off voltage to 0.05C for charge and discharge tests. Record the battery expansion data during the cycle.
[0076] Acupuncture: At ambient temperature, place batteries with different SOC on a horizontal surface, use a 4mm diameter needle to penetrate the center of the battery at a speed of 60mm / s, and record the battery surface temperature.
[0077] Hot box test: Place the fully charged battery in the test box, and raise the temperature of the test box to the hot box test temperature (130-140℃) at a rate of 5℃ / min. When the temperature reaches the test temperature, keep the temperature constant for 30 minutes. After the test, take out the battery and place it at an ambient temperature of 25±3℃ for 2 hours, and then visually inspect the battery appearance.
[0078] The test results are shown in Table 1:
[0079] Table 1
[0080]
[0081]
[0082] As can be seen from Table 1, from Examples 1-9, the cycle expansion rate of the battery made of the positive electrode sheet of the present invention can be controlled within 8%, the retention rate can reach more than 86%, the discharge rate can reach more than 92%, the rate charging capacity retention rate can reach more than 94%, and it will not catch fire or explode through the needle puncture test, the battery surface temperature can reach below 38°C, and the hot box test battery will not catch fire or explode; different positive electrode main materials and different proportions of composite flame retardants in the positive electrode sheet of the present invention will affect the battery performance. In Example 1, the cycle retention rate of the lithium cobalt oxide positive electrode main material is higher, the expansion rate is lower, the capacity is higher, and the temperature is lower. The increase in the proportion of halides in the composite flame retardant will result in a lower surface temperature of our needle puncture safety test battery.
[0083] By comparing Example 1 with Examples 4-5, it can be seen that the mass ratio of the initiator to the solid flame retardant in the positive electrode plate of the present invention will affect its performance. When the mass ratio of the initiator to the solid flame retardant is controlled at 1:(1-10), the performance of the positive electrode plate is better. If the proportion of the initiator is too low or too high, the cycle retention rate of the battery cell is lower, the expansion rate is higher, the capacity is maintained lower, and the temperature is also higher.
[0084] By comparing Example 1 with Examples 6-7, it can be seen that the mass ratio of the sulfur-based solid flame retardant and the halogen-based solid flame retardant in the positive electrode plate of the present invention will affect its performance. When the mass ratio of the sulfur-based solid flame retardant and the halogen-based solid flame retardant is controlled at 1:(1-10), the performance of the positive electrode plate is better. If the proportion of the sulfur-based solid flame retardant is too low or too low, the battery cell cycle retention rate is lower, the expansion rate is higher, the capacity is maintained lower, and the temperature is also higher.
[0085] By comparing Example 1 with Examples 8-9, it can be seen that in the positive electrode plate of the present invention, a flame retardant compounded with a sulfur-based solid flame retardant and a halogen-based solid flame retardant is used. During the heating process, the two flame retardants in the positive electrode plate can decompose to produce free radical scavengers and halogen ions, respectively. The combined action of the two substances can significantly improve the high temperature resistance of the positive electrode plate and the ability to block the chain reaction inside the battery, thereby achieving a safer effect.
[0086] By comparing Example 1 and Comparative Example 1, as well as Example 2 and Comparative Example 3, it can be seen that during the operation of the positive electrode plate of the present invention, the surface temperature changes. When the temperature reaches a certain temperature, the solid flame retardant can effectively play an insulating role at high temperature, and at the same time decompose at high temperature to produce free radical scavengers or halogen ions, thereby achieving a safety effect.
[0087] By comparing Example 1 and Comparative Example 2, and Example 2 and Comparative Example 4, it can be seen that the present invention adds an initiator to the positive electrode plate, and the initiator decomposes during the heating process of the plate. The decomposition product can accelerate the decomposition of the solid flame retardant to a certain extent to produce free radical scavengers or halogen ions, thereby further improving the stability of the positive electrode plate.
[0088] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer arranged on the surface of the positive electrode current collector; The positive electrode active material layer includes a positive electrode active material, a conductive agent, a binder, a solid flame retardant and an initiator.
2. The positive electrode sheet according to claim 1, characterized in that: The initiator includes any one of an azo initiator, an organic peroxide initiator or a redox initiator, or a combination of at least two thereof; Preferably, the azo initiator includes any one of azobisisobutyronitrile, azobisisoheptanenitrile or dimethyl azobisisobutyrate or a combination of at least two thereof; Preferably, the organic peroxide initiator comprises any one of benzoyl peroxide, tert-butyl perbenzoate or cyclohexanone peroxide, or a combination of at least two thereof; Preferably, the redox initiator comprises any one of potassium persulfate, thiol or sodium bisulfite, or a combination of at least two thereof.
3. The positive electrode sheet according to claim 1 or 2, characterized in that: The solid flame retardant includes a sulfur-based solid flame retardant and / or a halogen-based solid flame retardant, preferably a sulfur-based solid flame retardant and a halogen-based solid flame retardant; Preferably, the median particle size D50 of the solid flame retardant is 10 nm to 100 nm; Preferably, the mass ratio of the sulfur-based solid flame retardant to the halogen-based solid flame retardant is 1:(1-10); Preferably, the sulfur-based solid flame retardant includes triphenyl thiophosphate; Preferably, the halogen-based solid flame retardant includes brominated epoxy resin and / or brominated polystyrene.
4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The positive electrode current collector comprises aluminum foil; Preferably, the positive electrode active material comprises any one or a combination of at least two of a ternary nickel-cobalt-manganese positive electrode material, a cobalt-free positive electrode material, a lithium cobalt oxide positive electrode material, a lithium iron phosphate positive electrode material or a lithium-rich manganese-based positive electrode material; Preferably, the conductive agent comprises conductive carbon black and / or carbon nanotubes; Preferably, the binder comprises polyvinylidene fluoride.
5. The positive electrode sheet according to any one of claims 1 to 4, characterized in that: In the positive electrode active material layer, the mass ratio of the positive electrode active material, the conductive agent, the binder, the solid flame retardant and the initiator is (80-99):(0.1-10):(0.1-10):(0.1-10):(0.01-10).
6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The mass ratio of the initiator to the solid flame retardant is 1:(1-10).
7. A method for preparing a positive electrode sheet according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) mixing a positive electrode active material, a conductive agent, a binder, a solid flame retardant, an initiator and a solvent, and dispersing them to obtain a positive electrode slurry; (2) The positive electrode slurry is coated on the surface of the positive electrode current collector, and after post-treatment, the positive electrode sheet is obtained.
8. The preparation method according to claim 7, characterized in that: The solvent in step (1) comprises N-methylpyrrolidone; Preferably, the dispersing method in step (1) includes ball milling and / or ultrasonic dispersion.
9. The preparation method according to claim 7 or 8, characterized in that: The post-processing in step (2) includes drying, cold pressing and slitting.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as described in any one of claims 1 to 6.
Citation Information
Patent Citations
Method for improving lithium ion battery thermal stabilization through doping
CN101252189A
Maleimide additive for lithium battery and corresponding lithium battery anode formula
CN103050706A
Anode additive, preparation method of anode additive, anode plate and lithium ion secondary battery
CN107785578A
Preparation method of high-flame-retardancy lithium ion battery
CN109841908A
Electrode sheet, preparation method and application thereof
CN113036239A